SEBAB KERUNTUHAN SUATU BANGSA (Kajian Surat Al-Fajr Ayat 6-13) - Ismail, Hidayatullah Ismail; Fatah, Nasrul (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2018)
The writing aims to study about the last causes of a nation?s collapse which is contained in surah Al-Fajr was used thematic interpretation approach. As for the discussion was focused in verses 6-13. There were three languages that collapsed and destroyed in surah Al-Fajr, they were ?Ad, Tsamud and Fir?aun. These three nations were actually potraits of advanced nations and achieving high civilization, but their bad traits have delivered them to the detruction. These two bad traits were: the first was arrogance in the form of theological disobedience which include all of the denial of faith, blasphemy of religion and its symbols and treatise lie. The second, vandalism in the form of sosiological disobedience that include all of the destructive behavior such as intellectual brilliance, rebellion, persecution and criminalization of da?wah and tryrannical power.